CHEMICAL COMPOSITION OF SEPIA ORIENTALIS AND LOLIGO VULGARIS - PANDIT, A R; MAGAR, N G (Fishery Technology, 2016)
The chemical constituents of Sepia orientalis and Loligovulgaris weighing between 200-300g have been studied. It hasbeen found that these species could be classed as high protein andjow fat food and that these are good sources of calcium, phos~phorus, iron and moderate amounts of B-group vitamins.